Unseen dualities: underdiagnosis of substance use disorders in borderline personality disorder - Nabel, Jana; Bertele, Sebastian; Stapel, Britta; Scharn, Nicole; Kahl, Kai G. (Frontiers in Psychiatry, 2025)
IntroductionBorderline personality disorder (BPD) patients exhibit high rates of co-occurring mental disorders. Though literature reports varying prevalence of substance use disorders (SUD) in BPD, they are frequent with prevalence rates of approximately 45%. This study examines the 12-month prevalence of SUDs in a German sample of BPD patients by semi-structured interviews and compared to medical records.MethodsN=126 BPD patients were included. Twelve-month SUD prevalence was obtained by semi-structured clinical interview (SCID) and compared to reported prevalence in the general population and to diagnoses from medical records.ResultsMean age of the sample was 37.5 (SD ± 11.5) years and N=61 (48%) patients were female. Compared to the general population, increased 12-month prevalence based on SCID was found for alcohol abuse (22.2%, +7.9-times), alcohol dependence (17.5%, +5.6-times), cannabis abuse (15.1%, +30.2-times), cannabis dependence (19.0%, +31.7-times), sedative abuse (3.2%, +4.6-times) and sedative dependence (3.2% +4.6-times). N=43 (34.1%) patients presented at least one diagnosis of substance abuse and N=43 (34.1%) presented at least one diagnosis of substance dependence. N=51 (40.1%) patients were diagnosed with at least one substance use or dependence disorder. On average, prevalence based on SCID exceeded prevalence obtained from medical records. Particularly, alcohol abuse (3.5-times), cannabis abuse (2.4-times) and dependence (2.2-times), and sedative- and stimulant abuse (both no diagnosis in medical record vs. 3.2% in SCID) were underrecognized. Furthermore, concordance rates between diagnoses based on medical record and SCID were below 30% for all substances.ConclusionOur data confirm high prevalence of SUDs in BPD patients. Of note, medical records underrecognized alcohol abuse and cannabis abuse and dependence. Substance abuse and dependence are primary risk factors of suicidal behaviors and completed suicide. SUDs have been shown to be amenable to psychotherapeutic interventions. Therefore, careful diagnosis of SUD by e.g. expert structured interviews and integration of SUDs in a multimodal treatment plan is recommended.